Bacteria from four phylogroups of the Pseudomonas syringae complex can cause bacterial canker of apricot. (24th June 2019) - Parisi, L.; Morgaint, B.; Blanco‐Garcia, J.; Guilbaud, C.; Chandeysson, C.; Bourgeay, J. F.; Moronvalle, A.; Brun, L.; Brachet, M. L.; Morris, C. E.
Abstract : Pseudomonas syringae is described as a species complex, containing P. syringae ‐related species classified into 13 phylogroups and 23 clades. Pseudomonas syringae is one of the main pathogens of fruit trees, affecting nut trees, hazelnut and kiwi, pome and stone fruits. Bacterial canker of apricots is an important disease in regions of production with cold winters and conducive soils. This work characterizes the bacteria able to induce canker in apricots isolated in different French orchards. Bacteria from four phylogroups were able to induce canker. The pathogenicity to apricot was not linked to the pathogenicity to the three herbaceous species and cherry fruits tested, and was not always related to hypersensitive reaction on tobacco and ice nucleation activity. Bacteria pathogenic to apricot belong to phylogroups 01, 02, 03 and 07. The bacteria of phylogroups 01a and 07a ( Pseudomonas viridiflava ) characterized in this work have not previously been described as pathogenic to apricot.